Lupus Nephritis, the therapy and the role of Rituximab in resistant cases - Nasir, Hussein A.; Sharba, Yasir F.; Nasir, Nadia A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background Systemic lupus erythematosus (SLE) is a common autoimmune disease that affects mainly young females and nephritis is an important complication of the disease that may end with end stage renal disease (ESRD). Early diagnosis and proper treatment is important in decreasing the morbidity. Multiple immunesupressor agents used and according to the histopathology stage of the disease, still the proper drug used and the duration and dose required not settled. Rituximab which is monoclonal antibody that reacts against CD20 antigen on lymphocytes that cause B cells depletion is recently introduced in treatment of lupus nephritis . Objectives: to see the effect of different immunosuppressive agents in lupus nephritis and any response of resistant cases to Rituximab Methods sixty three systemic lupus erythematosus (SLE) patients’ age 3-45 years, 54 females and 9 males referred to the Nephrology Center in AL Sader Hospital in AL-Najaf governorate from April 2009- June 2013 enrolled in this study. All patients had renal biopsy and had categorized in different histopathological classes, the patients in stages I and II were treated with prednisolone while patients with other stages were treated with prednisolone and immunosuppressive therapy. The patients were followed up clinically and by laboratory results for response to the therapy, those who respond to the treatment tapering of the steroid was done and patients follow up were continued. Patients who showed no response to prednisolone or to the immunosuppressive agent were given Rituximab. Results –Mean age of patients was 22 years with a standard deviation+ 9 years. The association between sex and prednisolone was statistically not significant. The association between immunosuppressor therapy and sex was statistically not significant. The association between rituximab and sex was statically significant (p value 0.03(. The response to steroid therapy & age was statistically not significant. The association between response to immunosuppressor therapy and age was statistically not significant .The response to immunosuppressor therapy in different histopathological stages was statistically significant (P value 0.03). Response to Rituximab therapy was statistically significant (P value 0.048). Conclusion: Immunosuppressor therapy may have an effect in treatment of lupus nephritis and Rituximab may be useful in treatment of resistant cases of lupus nephritis.